2023
DOI: 10.3390/buildings13102552
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Beams Reinforced with Carbon 2D-Netzgitterträger Reinforcement

Nazaib Ur Rehman,
Marina Stümpel,
Harald Michler
et al.

Abstract: The increasing popularity of carbon-reinforced concrete (CRC) is attributed to its exceptional tensile properties, low density, no corrosion phenomenon, and remarkable flexibility, allowing it to be easily shaped into various forms. However, there is a pressing need to explore this innovative and sustainable alternative to traditional steel reinforcement. This motivates research and investigation of the feasibility of using a special 2D Netzgitterträger (NetzGT) reinforcement system, featuring a net-shaped fab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The study 32 showed, that the developed 2D net-shape NCF are suitable for the use as material efficient concrete reinforcement structure and opens new design and application possibilities for precast concrete structures in hollow-core slab for ceiling but also wall elements. 33…”
Section: Experimental Investigation Of the Load Bearing Behavior Of 2...mentioning
confidence: 93%
See 1 more Smart Citation
“…The study 32 showed, that the developed 2D net-shape NCF are suitable for the use as material efficient concrete reinforcement structure and opens new design and application possibilities for precast concrete structures in hollow-core slab for ceiling but also wall elements. 33…”
Section: Experimental Investigation Of the Load Bearing Behavior Of 2...mentioning
confidence: 93%
“…In order to evaluate the efficiency of the manufactured 2D net-shaped NCF as a concrete reinforcement structure, first investigation on the load bearing behavior have been performed by the Institute of Concrete Structures of the TU Dresden in a separate study which is presented in detail in. 32 Hereby yarn tensile test, single yarn pull-out test, tension tests (four-point bending test) and shear tests (three-point bending tests) on concrete embedded 2D net-shape reinforcement structures have been conducted.…”
Section: Experimental Investigation Of the Load Bearing Behavior Of 2...mentioning
confidence: 99%